Unveiling the Mysteries of Pharmacoreincarnation: A Study on the Spiritual and Metaphysical Dimensions of Using Psychoactive Drugs for Accessing Past Life Memories - Fendy Prasetyawan; Nanda Ardianto; Yuneka Saristiana; Wahyu Ariawan; Faisal Akhmal Muslikh; Yunita Dian Permatasari (Journal Health of Indonesian, 2023)
The research delves into the multifaceted realm of psychoactive drugs, spirituality, and the exploration of past life memories, known as "pharmacoreincarnation." Psychoactive substances like psilocybin, LSD, and DMT have gained attention for their profound alterations in consciousness and subjective experiences, often described as mystical or spiritual. Belief in reincarnation persists globally, fueled by anecdotal testimonials and cultural traditions. The study aims to explore pharmacoreincarnation through a comprehensive literature review and interdisciplinary perspective. Academic databases such as PubMed, PsycINFO, Scopus, and Google Scholar will be utilized to access relevant articles published in English within the last two decades. Thematic analysis will identify recurring themes and patterns across the literature, synthesizing findings to develop a coherent understanding of pharmacoreincarnation. The methodology involves systematic literature search, screening, and review processes to extract pertinent information aligned with the research objective. The synthesized findings will be organized into logical sections within the literature review, ensuring clarity and rigor. Peer review and revision will validate the quality and accuracy of the review before finalization. The study anticipates contributing significantly to knowledge on pharmacoreincarnation and its implications for consciousness studies, spirituality, and therapeutic practices. By embracing an interdisciplinary approach, it aims to unravel the underlying mechanisms of such experiences and their broader implications for personal identity and reality.